Upaya Meningkatkan Kinerja Karyawan yang Kondusif Pada PT. Mustika Jaya Lestari Melalui Motivasi Pelatihan dan Lingkungan Kerja - Wahyono, Anang Tri; Saptyana, Riska Fita; Fajrul, Muh.; Kaharudin, Erlitawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Employee performance, which is a reflection of individual competence in completing tasks, is a crucial factor for achieving organizational goals. This research aims to analyze the influence of motivation, training and work environment on the performance of PT Mustika Jaya Lestari. By using quantitative methods and saturated sampling techniques on 46 employees, this research found that motivation, training and work environment have a positive and significant influence on employee performance. This research recommends that companies continue to strive to increase employee motivation and suggests further research to consider other factors such as organizational culture.